Analisis Faktor-faktor Yang Mempengaruhi Produksi Padi di Kabupaten Langkat - Junita Lubis; Zulkarnaian Lubis; Zulkifli Lubis (Universitas Medan Area, 2018)
Langkat Regency is one of the national rice buffer. The rice needs is increasing every year, as well the population increasing. This study aimed to investigate the effect of the rice production input, land, labor, seed, and fertilizer, on the production of rice in Langkat Regency. Secondary data from 22 districts at Langkat Regency for two years (pooled data) was analyzed to answer the research objectives. The data analyzed with multiple regression by Coob-Douglas production function. The analysis showed that the positively significant impact of variables of land, labor, seed and fertilizer on the rice production. Production elasticity value is 1.671 (elastic). This generally means that rice farming in Langkat Regency in increasing returns to scale. Keywords: production, rice, input, scale, Langkat.